Cataract Surgery Results of New Lens Implantation “Synthesis” - E. A. Ivachev; I. P. Denisova; E. V. Anisimova; A. Yu. Krasnova (Oftalʹmologiâ, 2023)
Purpose. Analysis of the cataract surgery visual outcomes and advantages of intraocular lens Synthesis SIPY.Material and methods. We have operated 43 eyes with cataract (38 patients) using Synthesis SIPY lens. Non-corrected visual acuity was 0.13 ± 0.08, best corrected visual acuity (BCVA) was 0.36 ± 0.1.Results. Following 7 months, secondary cataract was not detected in any patient, what explain the actuality of square edge optical part on 360° of perimeter. The lens is inserted in cartridge in factory sterile conditions which exclude the contact between lens and environment, reduce the risk of incorrect inserting of the lens in cartridge following pinching by the cartridge flaps and, subsequently, the haptic tearing off. This complex “lens-cartridge” excludes the damage of haptics and optic parts, which can occur in using other IOLs during the removal of the lens from the vial and placing it in the groove of the cartridge. Position of cartridge in injector centralizes the cartridge tunnel for the Accuject Pro injector plunger, thereby reducing the risk of pinching the rubber tip of the IOL haptic plunger during implantation. The diameter of the cartridge tip allows the IOL to be implanted through a 1.6 mm tunnel. The uncorrected visual acuity after surgery was 0.6 ± 0.28. The best corrected visual acuity was 0.78 ± 0.24.Conclusions. The Synthesis SIPY lens has a number of advantages: factory installation of the lens into the cartridge and compatibility of the cartridge with the Accuject Pro injector prevent damage to the IOL; Implantation of the Synthesis SIPY lens is possible through the 1.6 mm corneal tunnel; high diopter ranges from -10.0D to + 40.0D allows for maximum visual results.